Text Theory in Contemporary Semitic Lingual Investigate “Speculate of the Questionable of the Conception, Definition and Term” - Kareem, Nadia Hamzah (International Journal of Psychosocial Rehabilitation, 2020)
The whole textual theory and Associated with it owes the efforts of triad polyglot studies are due Pioneers, who are Ferdinand de Saussure theoretician Semantic revolving around text and poetry And Roman Jacobson, who unsealed the entry to search in genre theory and in the relative metropolis of the literary phenomenon, and Emile Benveniste paved the way for comparative poetry and pragmatism of reading, in tripping of his researches into problems comparative Discourse exchange the bare of literary genres, particular, As two relatively unaffiliated structures and systems.